Cutaneous mastocytoma in dogs - Analysis of 10 cases diagnosed in Caxias do Sul (Research, Society and Development, 2022)
Mastocytoma is one of the most diagnosed skin neoplasms in dogs and occurs in all age groups. Due to the high incidence of this neoplasm, it is important to describe them in a macroscopic, histopathological way and also characterize dogs diagnosed with mastocytoma. The present work aims to produce a retrospective study conducted through the collection of records of 10 canine patients diagnosed with mastocytoma from a Veterinary Oncology service in the city of Caxias do Sul, Rio Grande do Sul, between January and December 2021. Information was collected regarding race, age group, gender, anatomical location of the neoplasm, tumor size, means of diagnosis and histological degree. Most of the dogs diagnosed were defined breed (7/10), females (6/10) and adults (5/10). The most recurrent anatomical location was the limbs (4/10). The nodulations were mostly 3 cm (6/10) size, which leads to a worse prognosis, in addition, 90% of the tumors were classified as grade II or low-grade. Evaluations of the surgical margins on histopathological examination showed that margins reduced to compromised margins. Thus, it is emphasized the need to have both specialized veterinarians and to have clarification scans to tutors to seek professionals how early the emergence of tumors to give accurate therapies, better life quality and prognosis to animals with neoplasms.